Operating Efficiency and Financial Performance of Deposit Money Banks in Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study has examined the influence of operating efficiency on the financial performance of Deposit Money Banks (DMBs) in Nigeria. Data used were extracted from the Annual Reports and Accounts of selected twelve (12) listed banks as on May 13, 2021 from 2011 to 2020. The Pearson Product Moment Correlation analysis was employed to determine the relationship between operating efficiency and financial performance of sampled banks. Panel Least Square regression was deployed to analyse the effect of operating efficiency on financial performance of the DMBs while the one-way ANOVA test was engaged in ascertaining significant differences in financial performances of the Systemically Important (D-SIBs) and the Non-Systemically Important (D-NSIBs) Banks. Findings revealed positive significant effect of operating efficiency on financial performance of all DMBs while there was no significant difference in the mean financial performances of the D-SIBs and D-NSIBs in Nigeria over the study period. It is therefore recommended that bank managements exercise due diligence in controlling operating costs of banks and Regulators should pay equal supervisory and regulatory attention to all banks without discrimination as all DMBs have the potential to exhibit systemic importance in the long run.